Optimasi Multiple Travelling Salesman Problem (M-TSP) Pada Angkutan Sekolah Dengan Algoritme Genetika (Studi Kasus: Yayasan Pembina Muslim Daarussalaam Sangatta) - Ageng Wibowo; Imam Cholissodin; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Pembina Muslim Daarussalaam Foundation is an educational institution located in Swarga Bara, North Sangatta, East Kutai Regency, East Kalimantan. The Foundation provides 8 school transports which are used to provide shuttle services for 160 Daarussalaam Islamic Kindergarten and Elementary students. The route for the shuttle is determined by the school transport driver. This research is conducted to determine the optimal shuttle route that will help school transport driver. The problem of this research is Multiple Traveling Salesman Problem (M-TSP) and one of the optimization methods that can help solve this problem is genetic algorithm. This research use a permutation representation, chromosome representation divided into 3 clusters, penjemputan (cluster 1), pengantaran 1 (cluster 2), and pengantaran 2 (cluster 3). Then the reproductive process is done by crossover with ordered crossover method and mutation with swap mutation method then the selection process is done by elitism selection method. With genetic algorithm that are 10.000 generations, population size 90, and combination of cr value = 0,6 and mr value = 0,4. The average fitness value in this research is 3,047. With the result of this research, Pembina Muslim Daarussalam Foundation can reduce the mileage by 400,82 KM and travel time around 877 minutes.